KEDISIPLINAN HIDUP DAN INTENSIFITAS PEMBINAAN IMAN KRISTEN BAGI PEMULIHAN KARAKTER PENGGUNA NARKOBA PADA YAYASAN MISI INDONESIA BREAKTHOUGH DI SENTUL CITY JAWA BARAT. - Hutabarat, Dr. Oditha R; Salim, Hockey; Sulistiyo, Samuel; Nauli, Jhonnedy Kolang; Simamora, Adolf Bastian (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2024)
The complexity of the negative impacts on drug users is related to risks to physical and mental health, socio-economic factors, as well as risks of addiction and criminality. The rehabilitation of drug users by the Indonesia Breakthrough Mission Foundation in Sentul, West Java, is based on the Bible. This study aims to examine the therapy patterns, particularly the application of values of Christian discipline in shaping the character of users. The research method used is descriptive qualitative and case studies on drug users. The results of this study show that discipline, applied by following the entire program intensively and strictly for 15 months for those with families and 18 months for those without families, can reshape a regular, obedient, and faithful lifestyle. Discipline is related to Christian faith values. Intensive and strict faith-building programs, such as Bible reading, sharing, Bible study, and regular prayer with the help of the Holy Spirit, restore drug users over a relatively long process. In conclusion, the programs designed by both government and private rehab institutions vary according to their Vision and Mission but are based on medical, psychological, sociological, legal, and theological studies.